Increased Expression of Syncytin-1 in Skeletal Muscle of Humans With Increased Body Mass Index - Ravichandran, Jayachandran; Roust, Lori R.; Katsanos, Christos S. (Frontiers in Physiology, 2022)
Obesity negatively impacts skeletal muscle protein metabolism, and also impairs skeletal muscle maintenance and regeneration. We analyzed muscle biopsy samples from humans with increased body mass index (BMI) (i.e. > 30 kg/m2) and controls (i.e., BMI < 25 kg/m2) for expression of syncytin-1, a fusogenic protein regulating skeletal muscle regeneration. When compared to controls, humans with increased BMI and concomitant reduction in muscle protein synthesis had higher expression of syncytin-1 in skeletal muscle (P < 0.05). Across human subjects, muscle protein synthesis correlated inversely (r = -0.51; P = 0.03) with syncytin-1 expression in muscle. Using a C2C12 cell line we found that expression of syncytin-A (i.e, corresponding protein in murine tissue) is increased by insulin, and that this response is impaired in the presence of fatty acids, whose metabolism is altered within the metabolic environment induced by increased BMI. In C2C12 cells, the response of the protein 4E-BP1, which signals increase in protein synthesis in muscle, resembled that of syncytin-A. These findings provide novel insights into the expression of syncytin-1 in skeletal muscle of humans with increased BMI, as well as its basic regulation by insulin and fatty acids in muscle. The findings signify the need for further research into the regulation of syncytin-1 in skeletal muscle of humans with increased BMI, as well as its biological implications for altering muscle protein metabolism and regeneration.